2017
DOI: 10.1186/s13071-017-2582-x
|View full text |Cite
|
Sign up to set email alerts
|

Hidden diversity of Nycteribiidae (Diptera) bat flies from the Malagasy region and insights on host-parasite interactions

Abstract: BackgroundWe present information on Nycteribiidae flies parasitizing the bat families Pteropodidae, Miniopteridae and Vespertilionidae from the Malagasy Region, contributing insight into their diversity and host preference.ResultsOur phylogenetic analysis identified nine clusters of nycteribiid bat flies on Madagascar and the neighbouring Comoros Archipelago. Bat flies sampled from frugivorous bats of the family Pteropodidae are monoxenous: Eucampsipoda madagascariensis, E. theodori and Cyclopodia dubia appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…(cf. fulvida ) and N. stylidiopsis , parasitizing both Myotis and Miniopterus [ 30 , 33 ]. In several cases, Penicillidia sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(cf. fulvida ) and N. stylidiopsis , parasitizing both Myotis and Miniopterus [ 30 , 33 ]. In several cases, Penicillidia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-two sites were visited from February 2012 to March 2013 in different areas of Madagascar to sample bats associated with taxonomic studies [ 25 ], ecology and distribution [ 27 ], as well as hosted ectoparasite and microparasites [ 30 33 ]. Bats were captured using mist nets and harp traps, which were most often placed at cave entrances or across bat flight pathways (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for a few disparate records of bat fly‐associated Laboulbeniales, virtually nothing is known about this triparatite system. Bat flies are dependent on their bat hosts (Ramasindrazana, Goodman, Gomard, Dick, & Tortosa, ) and it has been shown that habitat disturbance affects parasitism of bats by bat flies (Pilosof, Dick, Korine, Patterson, & Krasnov, ). The direction of the correlation (positive or negative) was reliant on the bat host species.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high specificity in the host-parasite interaction between bats and flies, some authors consider that this is probably not the result of a strict coevolution (Graciolli & Carvalho 2012). However, another study based on phylogenetic analyses of 15 bat host species parasitized by nine Nycteribiidae taxa found a significant signal of phylogenetic congruence (putative host-parasite coevolution) (Ramasindrazana et al 2017).…”
mentioning
confidence: 96%